Phytochemical analysis of Vietnamese propolis produced by the stingless bee Lisotrigona cacciae - Kristina Georgieva1; Milena Popova; Lyudmila Dimitrova; Boryana Trusheva; Le Nguyen Thanh; Diep Thi Lan Phuong; Nguyen Thi Phuong Lien; Hristo Najdenski; Vassya Bankova (My University, 2019)
Phytochemical analysis of Vietnamese propolis produced by the stingless bee Lisotrigona cacciae
Keywords: Phytochemical